Mendelian adult-onset leukodystrophy genes in Alzheimer´s disease. Critical influence of CSF1R and NOTCH3 - Sassi, C.; Nalls, M.A.; Ridge, P.G.; Gibbs, R.; Lupton, M.K.; Troakes, C.; Lunnon, K.; Al-Sarraj, S.; Brown, K.S.; Medway, C.; Lord, J.; Turton, J.; et al. (Elsevier, 2018)
Mendelian adult-onset leukodystrophies are a spectrum of rare inherited progressive neurodegenerative disorders affecting the white matter of the central nervous system. Among these, Cerebral Autosomal Dominant and Recessive Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL and CARASIL), Cerebroretinal vasculopathy (CRV), Metachromatic leukodystrophy (MLD), Hereditary diffuse Leukoencephalopathy with spheroids (HDLS), Vanishing white matter disease (VWM) present with rapidly progressive dementia as dominant feature and are caused by mutations in NOTCH3, HTRA1, TREX1, ARSA, CSF1R, EIF2B1, EIF2B2, EIF2B3, EIF2B4, EIF2B5, respectively. Given the rare incidence of these disorders and the lack of unequivocally diagnostic features, leukodystrophies are frequently misdiagnosed with common sporadic dementing diseases such as Alzheimer’s disease (AD), raising the question of whether these overlapping phenotypes may be explained by shared genetic risk factors. To investigate this intriguing hypothesis, we have combined gene expression analysis 1) in 6 different AD mouse strains (APPPS1, HOTASTPM, HETASTPM, TPM, TAS10 and TAU), at 5 different developmental stages (Embryo [E15], 2 months, 4 months, 8 months and 18 months), 2) in APPPS1 primary cortical neurons under stress conditions (oxygen-glucose deprivation) and single-variant and single-gene (c-alpha and SKAT tests) based genetic screening in a cohort composed of 332 Caucasian late-onset AD patients and 676 Caucasian elderly controls. Csf1r was significantly overexpressed (Log2FC>1, adj. p-val<0.05) in the cortex and hippocampus of aged HOTASTPM mice with extensive Aβ core dense plaque pathology. We identified 3 likely pathogenic mutations in CSF1R TK domain (p.L868R, p.Q691H and p.H703Y) in our discovery and validation cohort, composed of 465 AD and MCI Caucasian patients from the UK. Moreover, NOTCH3 was a significant hit in the c-alpha test (adj p-val = 0.01). Adult onset Mendelian leukodystrophy genes are not common factors implicated in AD. Nevertheless, our study suggests a potential pathogenic link between NOTCH3, CSF1R and sporadic LOAD, that warrants further investigation.